Plasticity of Dental Cell Types in Development, Regeneration, and Evolution - Krivanek, J; Buchtova, M; Fried, K; Adameyko, I (Journal of dental research, 2023)
Recent years have improved our understanding of the plasticity of cell types behind inducing, building, and maintaining different types of teeth. The latest efforts were aided by progress in single-cell transcriptomics, which helped to define not only cell states with mathematical precision but also transitions between them. This includes new aspects of dental epithelial and mesenchymal stem cell niches and beyond. These recent efforts revealed continuous and fluid trajectories connecting cell states during dental development and exposed the natural plasticity of tooth-building progenitors. Such "developmental" plasticity seems to be employed for organizing stem cell niches in adult continuously growing teeth. Furthermore, transitions between mature cell types elicited by trauma might represent a replay of embryonic continuous cell states. Alternatively, they could constitute transitions that evolved de novo, not known from the developmental paradigm. In this review, we discuss and exemplify how dental cell types exhibit plasticity during dynamic processes such as development, self-renewal, repair, and dental replacement. Hypothetically, minor plasticity of cell phenotypes and greater plasticity of transitions between cell subtypes might provide a better response to lifetime challenges, such as damage or dental loss. This plasticity might be additionally harnessed by the evolutionary process during the elaboration of dental cell subtypes in different animal lineages. In turn, the diversification of cell subtypes building teeth brings a diversity of their shape, structural properties, and functions.
Keywords: Animals; single-cell RNA-seq; regenerace; tooth development; developmental biology; zvířata; dental informatics/bioinformatics; Regeneration; zuby; cell differentiation; stem cell(s); Tooth